Noninvasive assessment of portal hypertension in patients with alcoholic cirrhosis - Tamara ALEMPIJEVI; Aleksandra SOKIC-MILUTINOVIC; Biljana MILICIC; Rada JESIC; Ana BALOVIC; Dragan POPOVIC; Miodrag KRSTIC (Turkish Journal of Gastroenterology, 2019)
-